Pembuatan dan Karakterisasi Membran Selektif Ion Timbal (II) dengan Menggunakan Etilen Diamin Tetra Asetat (EDTA) sebagai Ionofor - Waqifah, Ummul; Panggabean, Aman S.; Akkas, Erwin (Jurusan Kimia FMIPA UNMUL, 2017)
A research about preparation and characterization of Plumbum (II) ion selective membrane using a PVC based on ethylene diamine tetraacetate as ionophores have been done. Ethylene diamine tetra acetate (EDTA) was able to coordinate with Pb2+ and increase the conductivity of the membrane. Ethylene diamine tetra acetate (EDTA) as the main ingredient mixed with polyvinylchloride (PVC) as a matrix whose first dissolved using tetrahydrofuran (THF), added dioctyl phat alate (DOP) as a plasticizer. The membrane was soaked with Pb2+ for 2 days and membrane absorption ability of EDTA to the metal dopant Pb2+, and measured using atomic absorption spectrophotometer (AAS). Membrane absorption ability of the dopant metal Pb2+ retrieved the percent absorption was 76.01 % at the optimum composition of the membrane with a ratio of EDTA: PVC: DOP is 60: 30: 10. EDTA membrane characterization results with Fourier transform infrared spectroscopy (FT-IR) showed specific functional groups on the membrane EDTA.